2004
DOI: 10.1111/j.1365-2230.2004.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scrotal epidermolytic acanthomas; secondary to trauma?

Abstract: Epidermolytic hyperkeratosis (EH) is an abnormality of epidermal maturation, most commonly due to mutations in keratins 1 and 10, which may be a congenital or an acquired defect. The term epidermolytic acanthoma was applied to a solitary discrete epidermal proliferation characterized by EH. Subsequently there have been several reports of disseminated epidermolytic acanthomas. We report a rare case of multiple epidermolytic acanthomas localized to the scrotum. With the aetiology of epidermolytic acanthoma unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
(26 reference statements)
1
31
0
1
Order By: Relevance
“…Underlying implicated factors include ultraviolet radiation, immunosuppression, trauma, altered keratin expression and viral infection 14,16–20 . Association of EA with the former three factors has been described in anecdotal case reports 14,16,17,20 . Similar to bullous ichthyosiform erythroderma, which is characterized by decreased expression of keratins 1 and 10 secondary to genetic mutations, an immunohistochemical study on five solitary EAs demonstrated an abnormality in the expression of keratins 1 and 10 in lesional skin compared to adjacent normal skin 3,18 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Underlying implicated factors include ultraviolet radiation, immunosuppression, trauma, altered keratin expression and viral infection 14,16–20 . Association of EA with the former three factors has been described in anecdotal case reports 14,16,17,20 . Similar to bullous ichthyosiform erythroderma, which is characterized by decreased expression of keratins 1 and 10 secondary to genetic mutations, an immunohistochemical study on five solitary EAs demonstrated an abnormality in the expression of keratins 1 and 10 in lesional skin compared to adjacent normal skin 3,18 .…”
Section: Discussionmentioning
confidence: 98%
“…The etiopathogenesis of EA is not clear. Underlying implicated factors include ultraviolet radiation, immunosuppression, trauma, altered keratin expression and viral infection 14,16–20 . Association of EA with the former three factors has been described in anecdotal case reports 14,16,17,20 .…”
Section: Discussionmentioning
confidence: 99%
“…These mutations could be induced by numerous factors as UV radiation through intense sun exposure, [3] immunosuppression [4] or repeated trauma. [5,8] Electron microscopy demonstrates that the mechanism of blister formation is cytolysis rather than acantholysis. [7] Attempts to isolate human papilloma virus DNA, in biopsies of EA cases, have been negative.…”
Section: Case Report Case Reportmentioning
confidence: 99%
“…[2] The term EA is applied to discrete epidermal proliferations characterized by EH. EA has been described in different locations, namely eyelid, leg, anus, [2] abdomen, [3] back, [4] forearm, [4] scrotum [5] and the vulval region. [6,7] In a majority of the reports, the lesions are solitary, but multiple lesions have also been described, especially in the scrotum [5] and vulva.…”
Section: Case Report Case Reportmentioning
confidence: 99%
See 1 more Smart Citation